Evaluation of alcoholic extract of bamboo (Bamhusa arundinacea) buds on fracture healing in rabbit - HOQUE, M; MAITI, S K; HOQUE, N; SINGH, G R; AITHAL, H P; KUMAR, N; KALICHARNAN, KALICHARNAN (The Indian Journal of Animal Sciences, 2014)
The effect of alcoholib extract of bamboo (Bambtlsa arudinacea) buds on fracture healing was studied. Mid shaft simple transvers fractures were created in both the ulnae in 8 adults spayed female New Zealand White rabbits under thiopental anaesthesia. In test group of 4 animals, 1 M1 of the bamboo extract was injected subcutaneously on alternate days up to day 40-post fracture and the others kept as control. Clinically the animals of test group exhibited early weight bearing. Radiographs taken on 0, 10,20,30 and 40 day post-operatively revealed acceleration of fracture healing in test group. Histological examination of the biopsy sample collected on day 40 further confirmed the radiological findings. The animals of test group did not show any adverse effect of the extract.